Modern cronies southern industrialism from gold rush to convict labor, 1829-1894 - Wheeler, Kenneth H. (The University of Georgia Press, 2021)
Ararat -- A Railroad and Rowland Springs -- Iron -- The Education of Joseph E. Brown -- The Republic of Georgia -- Destruction -- Anew